PENELANTARAN ANAK PASCA PERCERAIAN ORANG TUA PERSPEKTIF HUKUM ISLAM DAN UNDANG-UNDANG POSITIF - Ahmad Sholeh Hasibuan; Nindi Aliska Nasution (HUKUMAH: Jurnal Hukum Islam, 2023)
ABSTRACTThis paper discusses the neglect of children after the parents divorce in terms of Islamic lawand the laws and regulations that apply in Indonesia. Every child born into the world must havehis rights. In Islam the maintenance of children is called Hadanah and in legal terms it is calledfoster care. In cases of divorce between husband and wife,it will be decided how the custody ofthe children resulting from their marriage will be decided. In Islam, the act of abandoningchildren is a prohibited act. Even though the law is not explained explicitly in the Qur'an andHadith, this violation is included in the ta'zir finger category where the punishment is left tothe government. According to the perspective of the Positive Law, people who neglect childrenwill receive sanctions for people who do it as regulated in the existing laws and regulations inIndonesia, perpetrators of child neglect will receive criminal sanctions for a maximum of 5(five) years and/or fines. a maximum of one hundred million rupiah.